From cytoplasm to environment: The inorganic ingredients for the origin of life - Novoselov, Alexey A.; Serrano, Paloma; Pacheco, Mírian Liza Alves Forancelli; Chaffin, Michael Scott; O'malley-James, Jack Thomas; Moreno, Susan Carla; Ribeiro, Filipe Batista [UNESP] (SAGE Publications, 2013)
Early in its history, Earth's surface developed from an uninhabitable magma ocean to a place where life could emerge. The first organisms, lacking ion transporters, fixed the composition of their cradle environment in their intracellular fluid. Later, though life adapted and spread, it preserved some qualities of its initial environment within. Modern prokaryotes could thus provide insights into the conditions of early Earth and the requirements for the emergence of life. In this work, we constrain Earth's life-forming environment through detailed analysis of prokaryotic intracellular fluid. Rigorous assessment of the constraints placed on the early Earth environment by intracellular liquid will provide insight into the conditions of abiogenesis, with implications not only for our understanding of early Earth but also the formation of life elsewhere in the Universe. Copyright © 2013, Mary Ann Liebert, Inc. 2013.
Keywords: Astrobiology; Early Earth; Hadean; Origin of life